1998
DOI: 10.1210/jc.83.4.1319
|View full text |Cite
|
Sign up to set email alerts
|

Human 17 -Hydroxysteroid Dehydrogenase Type 2 Messenger Ribonucleic Acid Expression and Localization in Term Placenta and in Endometrium during the Menstrual Cycle

Abstract: According to the current hypothesis, 17beta-hydroxysteroid dehydrogenases (17HSDs) regulate the extent of estrogen influence in the endometrium by converting estradiol (E2) locally into a biologically less active sex steroid, estrone (E1), and vice versa. Recently, we have shown that both 17HSD type 1 and type 2 are expressed in the human endometrium, and in the present work, using in situ hybridization, we show that 17HSD type 2 is localized in the glandular epithelial cells as previously shown for the type 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 0 publications
4
26
3
Order By: Relevance
“…Similar findings have been reported by several other investigators (11)(12)(13). 17␤HSD2 is localized exclusively in the glandular epithelial cells as demonstrated by immunohistochemistry (14) and in situ hybridization (15).…”
supporting
confidence: 92%
“…Similar findings have been reported by several other investigators (11)(12)(13). 17␤HSD2 is localized exclusively in the glandular epithelial cells as demonstrated by immunohistochemistry (14) and in situ hybridization (15).…”
supporting
confidence: 92%
“…In fact, interconversion activity has been reported in endometrial tissue (21). Expression of type 2 17h-hydroxysteroid dehydrogenases has been reported in glandular epithelial cells of cancer-free and malignant endometrium, whereas expression of type 1 17h-hydroxysteroid dehydrogenases has not been detected (22,23). The expression of other types of 17h-hydroxysteroid dehydrogenases has not h-hydroxysteroid dehydrogenases function in normal and cancer tissues of the endometrium remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously showed that 17bHSD2 mRNA level is higher in total villi samples from term placentas than from mid-gestation placentas, and that 17bHSD2 in endothelial cells of the villi might control the amount of active and inactive estrogens in the fetal circulation [10]. In addition, a higher abundance of 17bHSD2 in the endothelium of umbilical arteries at term also suggests that this enzyme could minimize the fetal contribution to the maternal rise in E 2 levels and also control the transfer of fetal androgens into the maternal circulation therefore, contributing to protect the maternal system against inappropriate androgenic effects [41,42].…”
Section: Discussionmentioning
confidence: 99%